A New Species of Tetraphyllidean (Cestoda) from the Largespot River Stingray, Potamotrygon falkneri (Potamotrygonidae: Chondrichthyes), from the Paraná Basin - Menoret, Adriana (2009)
Rhinebothrium paranaensis n. sp. (Tetraphyllidea: Cestoda) is described from the freshwater stingray Potamotrygon falkneri collected in the Colastine´ River, a tributary to the Lower Parana´ River in Argentina. The specimens were studied in detail using light and scanning electron microscopy and histology. Rhinebothrium paranaensis can be distinguished from all valid species in the genus using the following combination of characters: worm length, number of proglottids, diamond-shaped bothridia lacking constriction, number of loculi on the distal surface of bothridium, and the lack of vaginal sphincter and external seminal vesicle.